Pengaruh Instrumen Moneter Terhadap Indeks Saham Syariah Di Indonesia Tahun 2016-2021 - Novianti, Diah (Yayasan Literasi Sains Indonesia, 2022)
This study aims to examine the effect of monetary instruments, such as SBIS, Inflation, and Money Supply (JUB) on the growth of the Indonesian Sharia Stock Indeks (ISSI) in 2016-2022. This study uses multiple linear regression analysis using SPSS 26 to test the research hypothesis. The data used in this study are monthly data from SBIS yield data, inflation data, the Money Supply (JUB), as well as the ISSI monthly closing point index from January 2016 to December 2021.The results of this study indicate that partially there is an influence between SBIS and T test obtained a significance value of 0.001 < 0.05, , there is no partial effect between inflation based on the T test obtained a significance value of 0.082 > 0.05, and there is an influence between the Money Supply (JUB) based on the T test obtained a significance value of 0.000 < 0 .05 to the growth of the Indonesian Islamic stock index (ISSI) in 2016-2021. Simultaneously SBIS, Inflation and JUB, have an effect and are significant on the growth of ISSI in 2016-2021, with a value (Ftest 38.318 > Ftable 2.51) and a significance (0.000 <0.05).